1987
DOI: 10.1107/s0108270187088978
|View full text |Cite
|
Sign up to set email alerts
|

Structure du L-α-alaninate de cadmium trihydraté

Abstract: Abstract. [Cd(C3H6NOz)2].3H20 , M r --342.6, trigonal, P3121, a = 6.376 (3), c = 25.59 (2)/~, V= 901 (1) ,&3, Z=3, Dx=l.86(4)gcm -3, MoKa, 2=0.7107,/t, /1 = 18.4 cm -1, F(000) = 516, T= 298 K, R = 0.031, wR = 0.040 (w = 1) for 1109 independent reflexions. The metal coordination is octahedral; two alanine molecules are coordinated to the Cd atom as a bidentate ligand with a cis-O,O-trans-N,N donor set while the other two coordination positions are occupied by oxygen atoms of water molecules. The amino groups, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…The Cd−O bond distances are in the range from 2.225(3) to 2.354(3) Å, very similar to corresponding distances in other cadmium octahedral complexes including {Cd 2 (C 4 H 4 O 6 ) 2 (H 2 O)]·3H 2 O} n (2.188(3)−2.425(3) Å), the octahedral sites in Cd 2 (C 3 H 2 O 4 ) 2 (H 2 O) 4 (2.225(4)−2.296(4) Å), [Cd(C 3 H 6 NO 2 ) 2 ]·3H 2 O (2.296(4)−2.326(5) Å), Cd(C 4 H 2 O 4 )·2H 2 O (2.224(5)−2.521(5) Å), and the octahedral site in cadmium maleate (2.226(5)−2.317(5) Å) . Overall, the citrate ligand plays the role of a tridentate metal chelator, participating in the octahedral environment around Cd(II) and joining abutting Cd(II) ions in the lattice.…”
Section: X-ray Crystallographic Structuresupporting
confidence: 71%
“…The Cd−O bond distances are in the range from 2.225(3) to 2.354(3) Å, very similar to corresponding distances in other cadmium octahedral complexes including {Cd 2 (C 4 H 4 O 6 ) 2 (H 2 O)]·3H 2 O} n (2.188(3)−2.425(3) Å), the octahedral sites in Cd 2 (C 3 H 2 O 4 ) 2 (H 2 O) 4 (2.225(4)−2.296(4) Å), [Cd(C 3 H 6 NO 2 ) 2 ]·3H 2 O (2.296(4)−2.326(5) Å), Cd(C 4 H 2 O 4 )·2H 2 O (2.224(5)−2.521(5) Å), and the octahedral site in cadmium maleate (2.226(5)−2.317(5) Å) . Overall, the citrate ligand plays the role of a tridentate metal chelator, participating in the octahedral environment around Cd(II) and joining abutting Cd(II) ions in the lattice.…”
Section: X-ray Crystallographic Structuresupporting
confidence: 71%
“…The presence of two sites agrees with a doubling of all 13 C resonances observed for this complex by 13 C MAS NMR (not shown) considering observations made for the analogous Cd-alaninate, Cd-glycinate, and Zn-glycinate complexes. For these complexes the number of distinct 13 C carbonyl resonances matches the number of metal sites identified by XRD.
7 Experimental (a) and simulated (b−d) 67 Zn QCPMG spectra of Zn(Ala) 2 ·H 2 O. The experimental spectrum was obtained using τ 1 = τ 3 = 68.0 μs, τ 2 = τ 4 = 69.7 μs, τ a = 100 μs, τ d = 122 μs, ω rf /2π = 49.8 kHz, M = 19, a dwell time of 0.2 μs, and 589824 scans.
…”
Section: Resultsmentioning
confidence: 96%
“…For these complexes the number of distinct 13 C carbonyl resonances matches the number of metal sites identified by XRD. [28][29][30][31] To the best of our knowledge 87 Sr solid-state NMR has so far been employed only in a single study which specifically addressed the phase transition for strontium titanate (SrTiO 3 ) around 110 K. 54 In analogy to the examples discussed above, this is most likely ascribed to experimental difficulties that may be alleviated using the QCPMG method. This is illustrated by the experimental 87 Sr QCPMG NMR spectra of Sr(NO 3 ) 2 and SrMoO 4 shown in Figures 8a and 9a, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A symmetry check by PLATON (Spek 2009) showed that actually the orthorhombic symmetry is correct for both the zinc and cobalt salts. The same arrangement is found in the structure of bis(L-alaninato)-diaqua-cadmium monohydrate (Demaret and Abraham 1987b) Additionally, salts of alkali metals with serine and threonine were reported, but due to the lack of suitable crystals, no XRD experiments were conducted. Instead, (Fig.…”
Section: Serine and Threoninementioning
confidence: 54%